Artificial intelligence tools in Arabic learning content creation: evaluating the benefits and overcoming the challenges - Mahmod Attar Bashi, Zainab Senan; Sakka, Oula; Abdul Rahim, Elin Eliana (PENERBIT UniMAP, 2026)
The integration of artificial intelligence (AI) into content creation offers transformative potential for education, particularly in streamlining the production of animated learning materials. While educational animation is highly effective for simplifying complex subjects, its traditional production is often resource intensive. This paper explores the application of AI tools in creating an animated video to explain Hadith terminology to school students. It documents the end-to-end production process, from AI-assisted script generation to voice synthesis, to evaluate the practical benefits and challenges. The findings reveal that while AI significantly accelerates production, its use for Arabic-language Islamic content presents significant hurdles. These include cultural and stereotypical biases in datasets, inaccurate Arabic linguistic processing, inappropriate visual representations, and flawed text-to-speech pronunciation. The study concludes that while AI is a powerful tool for efficiency, its effective use in this context requires careful oversight and underscores the urgent need for developing culturally and linguistically nuanced AI models designed to Arabic Islamic education.